FACTORS HINDERING THE INTEGRATION AND POTENTIAL OF TECHNOLOGY IN EFL CLASSROOMS - Mali, Yustinus Calvin Gai (Sanata Dharma University Yogyakarta, 2025)
Teachers play essential roles in ensuring the success of technology integration and maximizing the potential of technology in theteaching and learning practices. Therefore, it is crucial to know somefactors that might hinder teachers from successfully integrating and fully maximizing technologys potential in various educational levels, such as those in English as a Foreign Language (henceforth called EFL) contexts. To achieve the objective of the study, the researcher examined twenty empirical research articles from sixteen peer-reviewed journals from 2009-2020 using Google Scholar, JSTOR, and ScienceDirect databases. The analysis results could be categorized into five main themes: (1) dealing with too many school administrative tasks, (2) lacking skills to use technology, (3) lacking relevant technology training, (4) dealing with constraints to join technology training, and (5) lacking access to technology. The discussions of each theme in light of the relevant literature, practical solutions to deal with the situations, and directions for further research are presented.